Pemanfaatan Digital Public Relations dalam Membangun Customer Engagement melalui Media Sosial Instagram @triindonesia (Studi Divisi Brand Communications PT Hutchison 3 Indonesia) - Samuel Ishak Putra; Nani Kurniasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Current technological developments make social media develop into one of the company's channels or brands to establish communication with its consumers. In social media as well, companies can build customer engagement effectively through a variety of communication messages which are packaged in the form of creative and interesting content. This study aims to find out the role of digital public relations at PT Hutchison 3 Indonesia in building customer engagement on social media, especially Instagram. The research approach used is descriptive qualitative with in-depth interview data collection methods and documentation. The results of the study indicated that useful of digital public relations Tri Indonesia plays an active role in building customer engagement on social media, by applying a balanced two-way communication model, even though the stage of customer involvement only reaches the curation stage.